Walking with Asafo in Ghana An Ethnographic Account of Kormantse Bentsir Warrior Music - Aduonum, Ama Oforiwaa (Eastman/Rochester Studies Ethnomusicology, 2022)
What is Asafo (music)? How and when is it performed? What is the state of this warrrior tradition that once served as the bedrock of the Akan, Ewe, and Ga societies in Ghana? How does Asafo enact the past and serve as an archive for the people? In an attempt to answer these questions, Walking with Asafo in Ghana investigates the musical pasts of Asafo. The book is an ethnography of walking, organized into eight chapters. Each chapter ends with a piece of creative writing in the author ethnographic voice in which she sums up the main ideas. It is Aduonum attempt at an anticolonial and decolonialist African musicology, one that subverts and decenters white racial framing of research, analysis, and presentation, disrupting how Euro-American concepts frame our ways of telling and experiencing Aduonum goal on this trajectory is to tell her story, create something new, and chart a new path. Through this fluid and complex book, she repositions African Elders&knowledge as epistemologies of decolonization and de-coloniality and centers the stories shared by local Fante scholars. The text is polyvocal, multimodal, multiperspective, performative, reflexive, and dialogic, informed by the structure of Asafo appellations, proverbs, her mentors tellings, and embodied" calling and responding. It is a performative scholarly discourse, based: a performance. As a celebration of Asafo, those warriors who insisted their lives matter, the text is meant to be read and performed.